Engineering hydrology an introduction to processes, analysis, and modeling - Jain, Sharad K.; Singh, Vijay P. (McGraw-Hill Education, 2019)
This comprehensive engineering textbook offers a thorough overview of all aspects of hydrology and shows how to apply hydrologic principles for effective management of water resources. It presents detailed explanations of scientific principles along with real-world applications and technologies. Engineering Hydrology: An Introduction to Processes, Analysis, and Modeling follows a logical progression that builds on foundational concepts with modern hydrologic methods. Every hydrologic process is clearly explained along with current techniques for modeling and analyzing data. You will get practice problems throughout that help reinforce important concepts.